FIELD LEVEL ENCRYPTION IMPLEMENTATION USING AES-256 FOR SECURE ACADEMIC INFORMATION SYSTEMS - Adi Fajaryanto Cobantoro; Elok Putri Nimasari; Sincan Maulana; Mohd Zuber; Shaikh Ameer (JIKO (Jurnal Informatika dan Komputer), 2026)
Data protection in higher education remains a pressing concern as student records and program registration data are frequent targets of cyber incidents. This paper presents the design and implementation of AES-256 to secure the registration feature within an academic information system (AIS). Specifically, this study delivers three main contributions: a modular cryptographic implementation at the controller level, a granular field-level encryption policy for sensitive attributes, and a validated security mechanism. We integrated a cryptographic module into a Fastify (Node.js) backend and PostgreSQL datastore. The results demonstrate the fulfillment of these contributions: first, the modular implementation effectively isolates encryption logic from the database layer; second, the field-level policy successfully secures sensitive PII while maintaining 100% query efficiency for non-sensitive data; and third, the security mechanism was validated through 17 white-box scenarios and dual-layer API testing. These results confirmed 100% functional correctness in encryption/decryption cycles and robust handling of invalid data inputs. The study contributes a practically deployable pattern for field level encryption in university information systems.